Factors that Influence Patient Perception of the Quality of Health Services - Isnanil Husna; Sumijatun Sumijatun; Tina Rosa (Indonesian Journal of Global Health Research, 2025)
Patient perception of hospital service quality is an important factor for the successful implementation of medical check-up units (MCU). This study aims to identify the influence of health service quality on patient perceptions at the MCU of Bhayangkara Hospital Level III Banda Aceh. The research method used is descriptive quantitative involving 90 patient respondents who have or are currently undergoing medical check-ups (MCU) at Bhayangkara Hospital Level III Banda Aceh through filling out questionnaires. Data analysis was performed using chi-square testing and multivariate ordinal logistic regression. The results showed that the majority of respondents were aged 18-28 years and most worked as freelancers/part-time workers. The results showed that most patients showed a good level of satisfaction with the quality of service at Bhayangkara Hospital. The service quality factors that were highly rated by patients were responsiveness (85.94%), assurance (85.10%), and empathy (84.29%). The results of multivariate ordinal logistic regression show that the Empathy dimension has the strongest influence (Exp(B) = 23.432), followed by Assurance (Exp(B) = 23.385), Real Evidence (Exp(B) = 23.268), Reliability (Exp(B) = 23.153), and Responsiveness (Exp(B) = 22.646). Based on these results, the factors that are considered quite low and need to be improved are real evidence and reliability.